2000
DOI: 10.3354/meps201091
|View full text |Cite
|
Sign up to set email alerts
|

Bio-optical characteristics of diatom and prymnesiophyte populations in the Labrador Sea

Abstract: During the spring of 1996, phytoplankton samples were collected along a transect from South Wolf Island (Labrador) to Cape Desolation (Greenland). Dense blooms of diatoms were found over the shelf near the coast of Labrador, whereas high concentrations of the colony-forming prymnesiophyte Phaeocystis pouchetii were found close to Greenland. Phytoplankton samples were separated into 2 major groups (diatoms or prymnesiophytes) on the basis of chlorophyll (chl) chl c 3 /chl a ratios (determined by HPLC analysis),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
69
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 54 publications
(99 reference statements)
15
69
0
1
Order By: Relevance
“…In agreement with previous studies, we found that phytoplankton communities dominated by diatoms had a high intracellular pigment concentration and low chl a-specific absorption coefficients (Stuart et al 2000). Although a significant variability has been found in pigment packaging and a* ph within diatoms (Finkel 2001), they generally consist of larger species (Fig.…”
Section: Effect Of Growth Conditions On the Chl A-specific Absorptionsupporting
confidence: 80%
“…In agreement with previous studies, we found that phytoplankton communities dominated by diatoms had a high intracellular pigment concentration and low chl a-specific absorption coefficients (Stuart et al 2000). Although a significant variability has been found in pigment packaging and a* ph within diatoms (Finkel 2001), they generally consist of larger species (Fig.…”
Section: Effect Of Growth Conditions On the Chl A-specific Absorptionsupporting
confidence: 80%
“…Stations in the central Labrador Sea (Stns 5,7,8 and 9) seemed to be dominated by haptophytes and also chlorophytes (Stns 5 and 7), whereas stations on the Labrador and Newfoundland shelves (Stns 3,10,11,13 and 14) were apparently dominated by diatoms and haptophytes. The presence of the haptophyte Phaeocystis sp., which may contain large amounts of fucoxanthin, has been reported in the Labrador Sea by Stuart et al (2000).…”
Section: Distribution Of the Main Phytoplankton Groups At The Dcmmentioning
confidence: 99%
“…The magnitude and the spectral shape of a* chl (λ) are known to vary greatly in response to differences in species composition, cell size, light history, and nutrient conditions in the field, and can even vary within species due to pigmentation and package effects associated with photoacclimation and physiological status (Sathyendranath et al 1987, Mitchell & Kiefer 1988, Sosik & Mitchell 1991, 1994, Kirk 1994, Bricaud et al 1995, Culver & Perry 1999, Stuart et al 2000. In addition, our results suggest that endoparasites may contribute significantly to variations in the magnitude and the shape of a* chl (λ) within species, particularly in midto late stages of infection.…”
Section: Parasitism and Its Photophysiological Implicationsmentioning
confidence: 99%